Multidisciplinary, patient-centred approach to improving compliance with venous thromboembolism (VTE) prophylaxis in a district general hospital. Issue 3 (19th July 2020) - Nana, Melanie; Shute, Cherry; Williams, Rhys; Kokwaro, Flora; Riddick, Kathleen; Lane, Helen
Abstract : Hospital-acquired venous thromboembolism (VTE) accounts for an estimated 25 000 preventable deaths per annum in the UK and is associated with significant healthcare costs. The National Institute for Health and Care Excellence guidelines on the prevention of VTE in hospitalised patients highlight the clinical and cost-effectiveness of VTE prevention strategies. A multidisciplinary quality improvement team (MD QIT) based in a district general hospital sought to improve compliance with VTE prophylaxis prescription to greater than 85% of patients within a 3-month time frame. Quality improvement methodology was adopted over three cycles of the project. Interventions included the introduction of a 'VTE sticker' to prompt risk assessment; educational material for medical staff and allied healthcare professionals; and patient information raising the awareness of the importance of VTE prophylaxis. Implementation of these measures resulted in significant and sustained improvements in rates of risk assessment within 24 hours of admission to hospital from 51% compliance to 94% compliance after cycle 2 of the project. Improvements were also observed in medication dose adjustment for the patient weight from 69% to 100% compliance. Dose adjustments for renal function showed similar trends with compliance with guidelines improving from 80% to 100%. These results were then replicated in a different clinical environment. In conclusion, this project exemplifies the benefits of MD QITs in terms of producing sustainable and replicable improvements in clinical practice and in relation to meeting approved standards of care for VTE risk assessment and prescription. It has been demonstrated that the use of educational material in combination with a standardised risk assessment tool, the 'VTE sticker', significantly improved clinical practice in the context of a general medical environment.